Guillain-Barré Syndrome after H1N1 Shot in Pregnancy: Maternal and Fetal Care in the Third Trimester—Case Report. (5th December 2012) - Campanharo, Felipe Favorette; Santana, Eduardo Felix Martins; Sarmento, Stephanno Gomes Pereira; Mattar, Rosiane; Sun, Sue Yazaki; Moron, Antonio Fernandes
Abstract : Guillain-Barré syndrome is a rare neurological disease of progressive installation, usually following a previous acute infectious state, has a rare incidence, especially in pregnancy, and can induce major complications and high mortality risk. Its occurrence, after immunization to influenza during the last trimester pregnancy, has not been reported before. We presented a case of a 36-year-old pregnant woman that was immunized to H1N1 in the last trimester; 10 days later she developed shoulder and lumbar spine's pain, limbs weakness and facial paralysis with unfavorable clinical evolution and was submitted to intensive therapy care. We described clinical and obstetrical approach, pointing out peculiarities involved in this pathology in pregnancy.